Merging Undergraduate Teaching, Graduate Training, and Producing Research: Lessons from Three Collaborative Experiments - Bolsen, Toby W.; Fairbanks, Bailey R.; Aviles, Eduardo E.; Pritchett, Reagan G.; Kingsland, Justin T.; LaPlant, Kristina M.; Montgomery, Matthew D.; Rogol, Natalie C. (PS, political science & politics, 2019)
Teaching undergraduate students, mentoring graduate students, and generating publishable research are distinct tasks for many political scientists. This article highlights lessons for merging these activities through experiences from an initiative that sparked a series of collaborative-research projects focused on opinions about crime and punishment in the United States. This article describes three collaborative projects conducted between 2015 and 2017 to demonstrate how to merge undergraduate teaching, graduate training, and producing research. By participating in these projects, students learned about social-scientific research through hands-on experiences designing experiments, collecting and analyzing original data, and reporting empirical findings to a public audience. This approach is an effective way to engage students and generate research that can advance professional goals.